Desvendando QR codes: uma aplicação dos códigos corretores de erros - Baroni, Carla (2023)
Motivated by the constant evolution of the means of information transfer and the effectiveness of quick response codes (QR Codes) in carrying out such transmissions with a low probability of message corruption, this essay seeks to characterize Error Correcting Codes, the technology responsible for this guarantee of reliability, applied to QR codes. This characterization begins with a brief description of barcodes and two-dimensional barcodes, the basis for characterizing the QR Code, whose components and creation history are discussed in greater depth. Subsequently, Error Correcting Codes are dealt with, followed by Reed-Solomon Codes (RS Codes), a specific category of the aforementioned codes applied to QR Codes.Regarding the RS Codes, the history of their development, as well as the mathematics behind them, are presented in different sections. Finally, the document includes an example of the application of RS codes and how they operate in the QR Codes.